Cognition, Metacognition and Learning - Amparo Acereda Extremiana (Ignatianum University Press, 2018)
This article presents a theoretical review of the difficulty that exists in our days to understand and apprehend metacognition, given the problem that involves the construct itself. In addition, it is a complex concept to measure and to be able to apply it to the educational world and the teaching-learning process. This article discusses the importance of cognition and metacognition, as it establishes a clear difference between the two. A theoretical review of metacognitive research is presented, differentiating the existing research studies on control and the cognitive regulation from the research work that examines metacognition in the educational field. This article also reflects on the state of the metacognitive measurement and the difficulties to capture the metacognitive magnitude and scale as it relates to the capability to transfer these concepts to the educational world. It discusses viable ways to achieve a better development of the autonomy of the apprentices, being reflected in a "learning to learn" action that transcends the school environment and projects to all facets of meaningful learning. Cognition, Metacognition and Learning